1994
DOI: 10.1007/bf01858010
|View full text |Cite
|
Sign up to set email alerts
|

Health belief model variables as predictors of screening mammography utilization

Abstract: Despite its efficacy, screening mammography is not widely utilized due to various factors. The Health Belief Model (HBM) has previously been used as one conceptualization of relevant patient attitudes. No psychometrically validated measure of these variables has previously been utilized, however, nor have prospective studies of women all of whom have been referred by their physicians for mammography been reported. The research reported here addressed both of those issues. A psychometrically validated measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…20 Mixed results of the association between perceived vulnerability and health behavior have been reported. 19,21,22 Chen et al reported a significant association between perceived vulnerability and getting a flu vaccine, 23 while Hyman et al 24 reported no association between perceived vulnerability and mammography utilization. Perceived severity concerns evaluations of both clinical and social consequences of a disease.…”
Section: Rogers'mentioning
confidence: 99%
“…20 Mixed results of the association between perceived vulnerability and health behavior have been reported. 19,21,22 Chen et al reported a significant association between perceived vulnerability and getting a flu vaccine, 23 while Hyman et al 24 reported no association between perceived vulnerability and mammography utilization. Perceived severity concerns evaluations of both clinical and social consequences of a disease.…”
Section: Rogers'mentioning
confidence: 99%
“…In Japan, Hata et al (2009) are proposing a revised HBM based on these basic concepts. In the past, studies on the association between breast cancer screening behaviors and psychological characteristic by the HBM have been conducted mainly in Europe and the United States (Stein et al, 1992;Hyman et al, 1994;Menon et al, 2007;Tavafian et al, 2009;Hajian et al, 2011;Yilmaz et al, 2013). In Japan, although there are reports on screening behaviors associated with population-based (Tohnai and Hata, 1994) and gastric cancer screenings (Tsubono et al, 1993), few have applied studies on breast cancer screening behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Inaccurate risk perceptions and elevated levels of distress may serve as barriers to mammography use in this population.6'7 Thus, interventions designed to improve risk comprehension, decrease distress, and enhance mammography use are needed.8…”
mentioning
confidence: 99%